2016
DOI: 10.1039/c6ra17613e
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Doped g-C3N4 film electrode: fabrication, characterization and photoelectrocatalysis property

Abstract: Ag-Doped graphitic carbon nitride films (Ag/g-C 3 N 4 ) were synthesized easily onto ITO substrates by a liquid-based reaction process. Ag/g-C 3 N 4 films were comprehensively characterized by SEM, HRTEM, XRD, UV/vis DRS, and XPS. The results indicated that Ag and Ag 2 O disperse homogeneously in the matrix of the g-C 3 N 4 film. The photocurrent response of the Ag/g-C 3 N 4 films increased remarkably with increasing Ag content and the best performance was observed with the sample of Ag/g-C 3 N 4 (1 : 10).The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The Ag‐g‐C 3 N 4 nanosheets was prepared according to the literature . Firstly, melamine powder (5.0 g) and 151 mg of silver nitrate (AgNO 3 ) were dissolved in 5 ml of water and ultrasonicated for 30 min to form a slurry.…”
Section: Methodsmentioning
confidence: 99%
“…The Ag‐g‐C 3 N 4 nanosheets was prepared according to the literature . Firstly, melamine powder (5.0 g) and 151 mg of silver nitrate (AgNO 3 ) were dissolved in 5 ml of water and ultrasonicated for 30 min to form a slurry.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have been devoted to improve the photocatalytic oxidation activity by modified g-C 3 N 4 using copolymerization, metal and anion doping and applying bias voltage etc. (Han et al, 2014;Hu et al, 2014;Qi et al, 2016;Yan et al, 2014;Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This XRD spectrum unambiguously confirmed that Eg-C 3 N 4 was self-assembled on CS. The AgNP/Eg-C 3 N 4 /CS nanocomposite showed several diffraction peaks at 37.95, 44.08, 64.27, and 77.33°, which are related to the (111), (200), (220), and (311) planes of the FCC structure of AgNPs, respectively. These were correlated with JCPDS card no. 01-089-3722 of AgNPs.…”
Section: Resultsmentioning
confidence: 62%